Terapia Comunitária Integrativa no sertão paraibano: avanços e desafios no contexto do SUS - Moraes, Marina Nascimento de (2014)
In 2008, the Integrative Community Therapy (ICT) reached several municipalities through an agreement between the Ministry of Health, Universidade Federal do Ceará and the Community Health Integrated Movement - MISMEC/CE, which aimed to conduct training in ICT with health professionals. In Paraíba, Trainer Polo MISC/PB was responsible for conducting two training classes in 2008 and 2009, involving thirteen cities in the countryside of Paraiba. Thus, we sought to evaluate the implementation process and continuity of ICT, linked to health services in the municipalities in the countryside of Paraiba, having specific objectives: to outline the professional profile of active therapists in the countryside of Paraiba; to identify the facilities, impasses and challenges faced by community therapists to perform ICT circles in their municipalities; and to evaluate the impact of training in ICT for practice and personal lives of therapists. This is a qualitative evaluative study, conducted in five municipalities in the countryside of Paraiba, which underwent training in Integrative Community Therapy and which had therapists who continued developing circles linked to health services. Seventeen community therapists were interviewed and for the analysis of the empirical material, it was used thematic content analysis on the transcribed interviews. All the research has met the requirements proposed by Resolution 466/12, with a favorable opinion of the Ethics Committee of Centro de Ciências da Saúde (CCS), CAAE: 15263813.3.0000.5188. It was found that the experiences of both the deployment and the continuity of this care tool had as major difficulties lack of support from the team and management, lack of adequate physical space, personal setbacks, obstacles due to policy issues and lack a reference person for the ICT within the municipality. However, support of different institutions, such as municipal management, the group of therapists, the USF team and the community in general, the impact of ICT in the community and therapists and the identification of the professionals with the proposed Integrative Community Therapy were listed as facilitator factors to surmount such difficulties, making it a positive experience that has brought several contributions to the lives of these therapists. The challenges listed were: returning to the realization of the circles with a frequency similar to the one in the time of implantation; expanding the ICT to different groups and spaces; and settling professionally in the municipality. The contributions that the training brought for personal development and practice of therapists were related to greater self-knowledge, improved interpersonal relationships, strengthen bonds and qualified hearing. It is concluded that this practice constitutes a careful technology, capable of offering spaces for speech and listening to the community in their several demands.